2017
DOI: 10.1103/physrevlett.118.245901
|View full text |Cite
|
Sign up to set email alerts
|

Filling-Fraction Fluctuation Leading to Glasslike Ultralow Thermal Conductivity in Caged Skutterudites

Abstract: It is generally believed that filling atoms randomly and uniformly distribute in caged crystals, such as skutterudite compounds. Here, we report first-principles and experimental discovery of a multiscale filling-fraction fluctuation in the RFe_{4}Sb_{12} system. La_{0.8}Ti_{0.1}Ga_{0.1}Fe_{4}Sb_{12} spontaneously separates into La-rich and La-poor skutterudite phases, leading to multiscale strain field fluctuations. As a result, glasslike ultralow lattice thermal conductivity approaching the theoretical minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 66 publications
3
29
0
Order By: Relevance
“…1 3 2reflections are clearly observed in Yb 0.9 Fe 3 CoSb 12 . These results suggest that a composite of two different skuttrudites was generated by MS and SPS due to uneven distribution of cations, and the formation of two different filled skutterudites has been reported previously [14][15][16][17][18]. The calculated lattice constants of the majority skutterudite (9.0820(1) Å for Yb 0.85 Fe 3 CoSb 12 and 9.0881(7) Å for Yb 0.9 Fe 3 CoSb 12 ) are smaller than those of the minority skutterudite (9.1659 5 (μHall) at 300 K by using a Hall measurement system (HMS-3000, Ecopia, Chandler Heights, AZ, USA) with a van der Pauw configuration.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…1 3 2reflections are clearly observed in Yb 0.9 Fe 3 CoSb 12 . These results suggest that a composite of two different skuttrudites was generated by MS and SPS due to uneven distribution of cations, and the formation of two different filled skutterudites has been reported previously [14][15][16][17][18]. The calculated lattice constants of the majority skutterudite (9.0820(1) Å for Yb 0.85 Fe 3 CoSb 12 and 9.0881(7) Å for Yb 0.9 Fe 3 CoSb 12 ) are smaller than those of the minority skutterudite (9.1659 5 (μHall) at 300 K by using a Hall measurement system (HMS-3000, Ecopia, Chandler Heights, AZ, USA) with a van der Pauw configuration.…”
Section: Resultssupporting
confidence: 82%
“…In PbTe-based TE alloys, this approach has been widely used with decomposition during the cooling process and resulted in the formation of nanocomposites with uniformly distributed nanoinclusions [12,13]. Recently, several studies for the preparation of bulk-type materials with multiple phases have been reported in La-, Ce-, and Yb-filled skutterudites mainly due to the uneven distribution of cations [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…15 This type of reduction was previously attributed to filling fraction fluctuation and consequent strain-field and long-range acoustic phonon scattering by Wei et al in La-filled Fe 4 Co 12 skutterudite. 17 In this work, we use mischmetal (Mm) as the source of filler elements, instead of pure rare-earth metals. n-Type Mm-filled CoSb 3 , with no charge-compensation by Fe doping, has not been studied until now: the description of n-type materials, is necessary together with the p-type counterparts for the development of proper thermoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
“…A novel guideline concept, phonon-glass and electron-crystal, is proposed to optimize thermoelectric performance (Slack and Rowe, 1995;Beekman et al, 2015). The previous studies have demonstrated that host-guest systems are ideal platform for this concept, such as clathrates (Takabatake et al, 2014), perovskites (Lee et al, 2017), and skutterudites (Ren et al, 2017), in which the lattice thermal conductivity (κ l ) can be dramatically reduced to a glass-like value while maintaining excellent electric properties. Because of their desirable thermoelectric behaviors, host-guest systems are identified as one of the most promising materials in practical thermoelectric applications.…”
Section: Introductionmentioning
confidence: 99%